Identifikasi Bakteri Staphylococcus sp. pada Luka Gangren Penderita Diabetes Mellitus - Sipayung, Apriska Dewi; Zebua, Winda Irawati; Arianto, Maniur; Zailani, Fadilah Khairah (FORIKES, 2025)
Diabetes mellitus is known as blood sugar disease or diabetes among the general public. The most common complication complained of by diabetes mellitus patients is gangrenous wounds on the feet and is difficult to heal due to microvascular complications that cause neuropathy or disorders of the peripheral nerves. Gangrenous wound infections are generally caused by Staphylococcus sp. bacteria. The purpose of this study was to observe the presence of Staphylococcus sp. bacteria in gangrenous wounds of diabetes mellitus patients undergoing examination in a clinical laboratory. The sample in this study amounted to 20 people taken by total sampling. This study was conducted using the culture method on blood agar media. Next, gram staining and catalase tests were performed. Then continued with bacterial identification using the Vitex 2 Compact tool. The analysis results showed that of the 20 samples cultured on blood agar media, 11 samples experienced the growth of round, milky white colonies, with the results of gram staining found purple coccus-shaped bacteria indicating gram-positive, the presence of gas bubbles in the catalase test was positive. In the Vitex 2 compact test, Staphylococcus aureus was found in 46% of 11 samples, Staphylococcus epidermidis in 27%, Staphylococcus haemolyticus in 18%, and Staphylococcus pyogenes in 9%. Furthermore, it was concluded that Staphylococcus sp. was the most common bacteria found in gangrenous wounds in patients with diabetes mellitus.Keywords: Staphylococcus aureus; diabetes mellitus; gangrenous wounds; blood agar ABSTRAK Diabetes mellitus dikenal dengan istilah penyakit gula darah atau penyakit kencing manis di kalangan masyarakat umum. Komplikasi paling sering dikeluhkan oleh pasien diabetes mellitus adalah luka gangren pada kaki dan sulit sembuh akibat komplikasi dari mikrovaskular yang menyebabkan neuropati atau gangguan pada saraf perifer. Infeksi luka gangren tersebut umumnya disebabkan oleh bakteri Staphylococcus sp. Tujuan studi ini adalah melihat keberadaan bakteri Staphylococcus sp. pada luka gangren penderita diabetes mellitus yang menjalani pemeriksaan di laboratorium klinik. Sampel pada penelitian ini berjumlah 20 orang yang diambil secara total sampling. Penelitian ini dilakukan dengan metode kultur pada media blood agar. Selanjutnya dilakukan pewarnaan gram, dan uji katalase. Kemudian dilanjutkan dengan identifikasi bakteri menggunakan alat Vitex 2 Compact. Hasil analisis menunjukkan bahwa dari 20 sampel yang dikultur pada media blood agar, 11 sampel mengalami pertumbuhan koloni bulat berwarna putih susu, dengan hasil pewarnaan gram ditemukan bakteri bentuk coccus bergerombol berwarna ungu menandakan gram positif, adanya gelembung gas pada uji katalase positif. Pada uji vitex 2 compact dari 11 sampel ditemukan bakteri Staphylococcus aureus sebanyak 46%, Staphylococcus epidermidis 27%, Staphylococcus haemolyticus 18%, Staphylococcus pyogenes 9%. Selanjutnya disimpulkan bahwa Staphylococcus sp merupakan bakteri terbanyak yang terdapat pada luka gangren penderita diabetes mellitus.Kata kunci: Staphylococcus aureus; diabetes mellitus; luka gangren; blood agar